Carbon Dioxide Emissions from Electricity Power Generation and Economic Growth in South Africa - Hlongwane, Nyiko Worship; Daw, Olebogeng David (International Journal of Energy Economics and Policy, 2022)
This study analyses the relationship between CO2 emissions from electricity generation and economic growth in South Africa. The study utilises annual time series data spanning for the period from 1971 to 2014 sourced from the World Bank. The study employs a Vector Error Correction Model (VECM) to analyse the short run and long run relationships. Empirical results revealed that there is a negative statistically insignificant short run relationship and long run negative statistically significant relationship between CO2 emissions and economic growth in South Africa. The Granger causality results revealed noncausal relationship between CO2 and economic growth. The policy implication of this study is that Eskom and policy makers must propose and implement policies aimed at reducing CO2 emissions from electricity generation as it will improve economic growth in South Africa.